Analisis Sistem Pengelolaan Limbah B3 Di Industri Tekstil Kabupaten Bandung - Eka Wardhani; Dea Salsabila (Rekayasa Hijau : Jurnal Teknologi Ramah Lingkungan, 2021)
ABSTRAKPenelitian ini bertujuan untuk mengetahui pengelolaan LB3 yang telah dilakukan di indsutri tekstil. Metode penelitian menggunakan metode perbandingan antara kondisi di lapangan dengan peraturan yang berlaku. Berdasarkan hasil evaluasi mengenai pengelolaan LB3 yang dilakukan oleh PT X dapat disimpulkan beberapa hal yaitu sumber LB3 berasal dari proses produksi, lumpur IPAL, boiler, labolatorium, pemeliharaan mesin, dan klinik. Jenis LB3 yang dihasilkan berasal dari sumber spesifik umum yaitu lumpur IPAL dan limbah medis, sumber spesifik khusus yaitu hanya fly ash dan sumber tidak spesifik yang meliputi lampu TL, drum bekas LB3, oli bekas dan reagen. Karakteristik LB3 terdiri dari beracun, mudah menyala, korosif dan infeksius. PT X telah melakukan pengelolaan LB3 yang meliputi aspek pengemasan dan pewadahan, pengumpulan, penyimpanan, pengangkutan dokumen pengelolaan LB3, dan pelabelan LB3. Untuk kegiatan pengangkutan PT X bekerja sama dengan pihak ketiga diantaranya adalah PT Hijau Lestari, PT PPLI, PT Khalda, dan WGI. Berdasarkan hasil analisis pengelolaan LB3 di perusahaan ini termasuk kategori baik. Upaya pengelolaan LB3 yang harus ditingkatkan yaitu pada proses pelekatan simbol dan label, pengemasan, dan penyimpanan LB3.Kata Kunci: Kabupaten Bandung, Industri Tekstil, Limbah B3,ABSTRACTThis study aims to determine the management of LB3 that has been carried out in the textile industry. The research method uses a comparison between conditions in the field and applicable regulations Based on the evaluation results on the management of hazardous materials carried out by PT X, it can be concluded several things, namely the source of hazardous materials originating from the production process, sludge from the wastewater treatment plant, boilers, laboratory, engine maintenance, and clinics. The types of hazardous materials produced come from general specific sources such are sludge from the wastewater treatment plant and medical waste, specific sources which are fly ash and non-specific sources which include lamps, drums used in hazardous materials, used oil and reagents. The characteristics of hazardous materials consist of toxic, flammable, corrosive, and infectious. PT X has managed the management of hazardous materials which includes aspects of packaging, storage, collection, storage, transportation of documents on the management of hazardous materials, and labeling of hazardous materials. For transportation activities, PT X cooperates with third parties including PT Hijau Lestari, PT PPLI, PT Khalda, and WGI. Based on the analysis the achievement of the management of dangerous substances in this company including the good category. Efforts to manage toxic and hazardous materials must be improved in the process of sticking symbols and labels, packaging, and storing toxic and hazardous materials.Keywords: Bandung Regency, Testile iIndustry, hazardous waste materials